2017
DOI: 10.1016/j.celrep.2017.11.045
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA Panct1 Maintains Mouse Embryonic Stem Cell Identity by Regulating TOBF1 Recruitment to Oct-Sox Sequences in Early G1

Abstract: Long noncoding RNAs (lncRNAs) have been implicated in diverse biological processes, including embryonic stem cell (ESC) maintenance. However, their functional mechanisms remain largely undefined. Here, we show that the lncRNA Panct1 regulates the transient recruitment of a putative X-chromosome-encoded protein A830080D01Rik, hereafter referred to as transient octamer binding factor 1 (TOBF1), to genomic sites resembling the canonical Oct-Sox motif. TOBF1 physically interacts with Panct1 and exhibits a cell-cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 33 publications
0
25
2
Order By: Relevance
“…However, our IWP2 treatment results ( Supplementary Figure 6c) indicate that these upregulated Wnts may not be suffficient to maintain gastric regeneration. It has been reported that Bclaf3 binds to the Oct-Sox binding motif and is necessary to maintain pluripotency of mouse embryonic stem cells (mESCs) (24). In contrast to this report, we find that Bclaf3 expression is present in non-stem cells and may induce differentiation in gastric glands by supressing Wnt signalling and Reg family genes.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our IWP2 treatment results ( Supplementary Figure 6c) indicate that these upregulated Wnts may not be suffficient to maintain gastric regeneration. It has been reported that Bclaf3 binds to the Oct-Sox binding motif and is necessary to maintain pluripotency of mouse embryonic stem cells (mESCs) (24). In contrast to this report, we find that Bclaf3 expression is present in non-stem cells and may induce differentiation in gastric glands by supressing Wnt signalling and Reg family genes.…”
Section: Discussioncontrasting
confidence: 99%
“…ESCs are an excellent in vitro model for studying the role of lncRNAs in pluripotent cells and cellular differentiation [ 13 , 14 ]. To identify lncRNAs participating in mESC pluripotency and lineage differentiation, we analyzed the transcriptome of mESCs during differentiation [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, identifying additional X-linked regulators that mediate the effects X-dosage in pluripotent stem cells requires future investigations [10]. An interesting additional candidate is the recently-identified X-linked transient octamer binding factor 1 (TOBF1) [53], since it was shown to sustain pluripotency. It is also possible that other regulators of the Erk pathway are involved.…”
Section: Impact Of Impact Of Dusp9 Dusp9 Dosage On the Molecular And mentioning
confidence: 99%